KONSEP DASAR PENGELOLAAN DI KELOMPOK BERMAIN AMALIA - Yolanda Arta Mefia; Retno Wulandari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
In this study, we will discuss the Basic Concepts of Playgroup Management which are important in carrying out activities in an institution. This study aims to describe the planning, organizing, implementation, supervision and assessment of the play group. This research uses a descriptive method with a qualitative approach, while the subjects of this study include administrators and students. Data collection techniques used are interviews, observation, and documentation. The results of this study are to find out more about the management of Playgroups. The background of this research is to see the number of playgroups that have been established and to find out how the playgroups are managed.